Fluoroscopy-Guided Resolution of Ingested Thrombus Leading to Functional Disturbance of a Continuous-Flow Left Ventricular Assist Device - Jens Garbade; Hartmuth B. Bittner; Friedrich-Wilhelm Mohr; Markus J. Barten (Case Reports in Surgery)
The third generation of left ventricular assist devices (LVADs) has been shown to improve outcome and quality of life in patients suffering from acute and chronic heart failure. However, VAD-associated complications are still a challenge in the clinical practice. Here we report the resolution of a mobile thrombus formation in the proximity of the inflow cannula of a third generation of LVADs (HVAD Pump, HeartWare, Inc.) in a patient with chronic heart failure 4 months after implantation.